Plant-Based Meat Alternatives and Their Impacts on the US Meat Market. - Křepelka, Jakub (2025)
This thesis explores the rise of plant-based meat alternatives (PBMAs) and their impact on the traditional meat industry in the United States. This study includes research on market trends, consumer behavior, and industry responses to the popularity shifts of PBMAs. The research is structured around one main research question: How have the emerging PBMAs affected the structure, operations, and responses of the traditional meat industry? It further uses the following questions to achieve the objective: What are the economic and cultural foundations of the U.S. meat industry? What are the main drivers behind PBMA’s adoption? What are the strategic responses of the companies operating in the traditional meat market? The thesis findings indicate that even though the PBMAs have not yet significantly displaced traditional meat, they are changing the industry practices, strategies, and consumer expectations. The conclusion of the research is that PBMAs represent both a challenge and an opportunity for the U.S. meat industry. The future outcomes will depend on innovation, regulation trends, and consumer acceptance.